PROBLEMS OF NON-PAYMENT OF POPULATION FOR ELECTRIC ENERGY - N. Gergert; N. Lubimova (Вестник университета)
Current state of the debt of population for electricity has been described, the methods of struggle of power companies and regulatory agencies with its growth in Russia have been considered. The reasons for non-payment of population and their share in the structure of total debt for electricity in 2014-2017 have been analyzed. The ways of struggle with non-payment of the population for energy in a number of foreign countries have been highlighted. The prospects for the application of foreign experience in Russia have been considered in terms of methods of regulating the growth of the debt of population for electricity